The training of specialist doctors in spain : Historical outline and current status - Aguayo-Albasini, José Luis (Spanish Journal of Medical Education, 2020)
A historical sketch of the training process for specialist doctors in Spain is presented: the socalled MIR system, a supervised and paid system for the acquisition of competencies. It was not until the end of the 70s of the last century when an extraordinary development of the residence system began throughout the country, which became exclusive. Until then, the achievement and practice of a medical specialty generally lacked guarantees. Today there is an accredited and solid hospital structure for the training of medical specialists (which has been extended to other health professions) and a regulation of the teaching bodies that strictly guarantees the process. The system maintains aspects that could be improved Key words: Medical education, medical specialization, posgratuate training